Managing Financial Risks in indebted Developing Countries : Occa Paper No.65. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1989)
This paper examines the types of market-related hedging instruments that could potentially be useful to indebted developing countries as they seek to manage the financial risks created by variability of the prices of external assets and commodities. The paper reviews the variability in interest rates, exchange rates, and prices of primary commodities and then analyzes the effects of this variability on the domestic and external performance of indebted developing countries. Market-related hedging instruments that are accessible to indebted developing countries are also examined.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet